Extracellular matrix and the neural stem cell niche - Kazanis, Ilias (Dev Neurobiol, 2011)
Basal lamina is present in many stem cell niches, but we still have a poor understanding of the role of these and other extracellular matrix components. Here we review current knowledge regarding extracellular matrix expression and function in the neural stem cell niche, focusing on the subependymal zone of the adult CNS. An increasing complexity of extracellular matrix molecules has been described, and a number of receptors expressed on the stem cells identified. Experiments perturbing the niche using genetics or cytotoxic ablation of the rapidly dividing precursors, or using explant culture models to examine specific growth factors, have been influential in showing how changes in these extracellular matrix receptors regulate neural stem cell behaviour. However the role of changes in the matrix itself remains to be determined. The answers will be important, as they will point to the molecules required to engineer niches ex-vivo so as to provide tools for regenerative neuroscience.